GAYA KEPEMIMPINAN TRANFORMASIONAL DALAM MEMPENGARUHI KINERJA KOPERASI - Nur Azizah Zuhriyah (LPPM Politeknik Pratama, 2023)
This study aims to analyze the influence of transformational leadership style on cooperative performance. Transformational leadership is measured based on three main dimensions, namely intellectual stimulation, inspirational motivation, and idealized influence, which have been adapted from the Bass and Avolio (2014) model. Data were collected through a survey of cooperative administrators and analyzed using a quantitative method with the Partial Least Square (PLS) approach. The results of the study showed that transformational leadership has a positive and significant influence on cooperative performance of 28.3%, with the main indicators that have an influence being working effectively and efficiently, having a clear vision and mission, and providing encouragement to subordinates. This finding is in line with previous studies which state that transformational leadership can increase organizational productivity and effectiveness. However, the main challenge in cooperatives is the lack of accountability of administrators, especially in the implementation of the Annual Members Meeting (RAT). Therefore, it is necessary to increase the capacity of management leadership and strengthen cooperative governance to be more transparent and professional. With effective leadership, cooperatives can develop more competitively and provide economic benefits to their members and the community.